Antioxidant Naturally Occurring Pleiotropically Acting Bioactive Compounds, as Polymeric Nanotherapeutics Against Autoimmune Diseases Progression - Panagiotis Theodosis-Nobelos; Fani-Niki Varra; Michail Varras; Georgios Papagiouvannis; Eleni A. Rekka (Current Issues in Molecular Biology)
Autoimmune diseases are driven by chronic inflammation and oxidative stress, thus requiring innovative therapeutic approaches. Polymeric nanotherapeutics incorporating antioxidant bioactive compounds offer a promising strategy for immune modulation and enhanced drug delivery. This review explores the application of polymer-based nanocarriers for improving the solubility, bioavailability, and targeted delivery of antioxidant compounds in autoimmune disease treatment. A comprehensive analysis of recent advancements in polymeric nanoformulations, including poly(lactic-co-glycolic acid) (PLGA), polyethylene glycol (PEG), chitosan, and hyaluronic acid, was conducted. The therapeutic efficacy of various antioxidant-loaded nanoparticles has been assessed in both preclinical and clinical studies. Phenolic antioxidants, such as resveratrol, curcumin, quercetin, and epigallocatechin-3-gallate, exhibit potent anti-inflammatory effects; however, their poor solubility limits their clinical application. Nanocarriers such as dendrosomes, tannic acid-based reactive oxygen species (ROS)-scavenging nanoparticles, and folic acid-functionalized systems enhance drug stability, controlled drug release, and macrophage targeting. Carotenoid and bilirubin nanoparticles further demonstrate immunomodulatory effects in multiple sclerosis, psoriasis, rheumatoid arthritis, and inflammatory bowel disease. Polymeric antioxidant nanotherapeutics provide targeted and sustained drug delivery, offering improved efficacy and reduced toxicity. Future research should focus on optimizing these nanocarriers for clinical translation and patient-centered therapeutic strategies.